2007
DOI: 10.1158/1078-0432.ccr-07-0247
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Efficacy of a Single Dose of the Bisphosphonate Zoledronic Acid

Abstract: Purpose: Bisphosphonates play a central role in the management of bone loss due to a range of disorders, including metastatic bone disease, cancer treatment^induced bone loss, and postmenopausal osteoporosis. With potent bisphosphonates, such as zoledronic acid, it may be possible to maintain efficacy with relatively infrequent administration.Experimental Design: Sixty-six patients who were osteopenic at >1 year following curative cancer therapy received a single i.v. 4 mg dose of the bisphosphonate zoledronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…In another series of patients who received bisphosphonates (not ZOL) within 12 months of conception or during the first trimester of pregnancy (n = 21), no increased risk of birth defects was seen [29]. We could not find any published reports regarding exposure to ZOL and pregnancy outcome, but concerns regarding foetal development remain because of the potency and long offset duration of ZOL [31].…”
Section: Discussionmentioning
confidence: 81%
“…In another series of patients who received bisphosphonates (not ZOL) within 12 months of conception or during the first trimester of pregnancy (n = 21), no increased risk of birth defects was seen [29]. We could not find any published reports regarding exposure to ZOL and pregnancy outcome, but concerns regarding foetal development remain because of the potency and long offset duration of ZOL [31].…”
Section: Discussionmentioning
confidence: 81%
“…Recently, the bisphosphonate zoledronic acid (ZOL) has been approved for the treatment of osteoporosis due to its beneficial effect on bone mass [14,15]. This drug has a high affinity for hydroxyapatite and binds directly to mineralized bone [16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that zoledronic acid therapy can also augment erythropoetic activity [20] and that even after cessation of zoledronate therapy there continues to be a long-term improvement in BMD [21]. The latter finding is especially important in the light of other observations [36,37], which suggest that it may be possible to reduce the cost of zoledronate therapy by reducing the number of zoledronate doses. Recent data also suggest that the efficacy of zoledronate therapy might depend on the other genotypes like that in the genes encoding the vitamin D receptor [15] and bone type I collagen [23].…”
Section: Discussionmentioning
confidence: 97%